Effects of immediate postexercise carbohydrate ingestion with and without protein on neutrophil degranulation - Costa, R. J. S.; Walters, R.; Bilzon, J. L. J.; Walsh, N. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
The purpose of the study was to determine the effects of carbohydrate (CHO) intake, with and without protein (PRO), immediately after prolonged strenuous exercise on circulating bacterially stimulated neutrophil degranulation. Twelve male runners completed 3 feeding interventions, 1 week apart, in randomized order after 2 hr of running at 75% VO2max. The feeding interventions included a placebo solution, a CHO solution equal to 1.2 g CHO/ kg body mass (BM), and a CHO-PRO solution equal to 1.2 g CHO/kg BM and 0.4 g PRO/kg BM (CHO+PRO) immediately postexercise. All solutions were flavor and water-volume equivalent (12 ml/kg BM). Circulating leukocyte counts, bacterially stimulated neutrophil degranulation, plasma insulin, and cortisol were determined from blood samples collected preexercise, immediately postexercise, and every 30 min until 180 min postexercise. The immediate postexercise circulating leukocytosis, neutrophilia, and lymphocytosis (p < .01 vs. preexercise) and the delayed lymphopenia (90 min postexercise, p < .05 vs. preexercise) were similar on all trials. Bacterially stimulated neutrophil degranulation decreased during recovery in control (23% at 180 min, p < .01 vs. preexercise) but remained above preexercise levels with CHO and CHO+PRO. In conclusion, CHO ingestion, with or without PRO, immediately after prolonged strenuous exercise prevented the decrease in bacterially stimulated neutrophil degranulation during recovery.